2018
DOI: 10.1167/18.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Weighted integration of short-term memory and sensory signals in the oculomotor system

Abstract: Oculomotor behaviors integrate sensory and prior information to overcome sensory-motor delays and noise. After much debate about this process, reliability-based integration has recently been proposed and several models of smooth pursuit now include recurrent Bayesian integration or Kalman filtering. However, there is a lack of behavioral evidence in humans supporting these theoretical predictions. Here, we independently manipulated the reliability of visual and prior information in a smooth pursuit task. Our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 66 publications
4
35
0
Order By: Relevance
“…Orban de Xivry et al (2013) demonstrated that Kalman filtering can reproduce the major properties of visually guided smooth pursuit and anticipatory smooth pursuit. A later study demonstrated that the reliability-based integration of prior expectation with visual information occurred not only in smooth pursuits but also in catch-up saccades (Deravet et al, 2018). Similarly, Bogadhi et al (2013) demonstrated that the reliability-weighted dynamic integration of retinal and extra-retinal signals can explain pursuit behaviors during target blanking.…”
Section: Cognitive Control and Bayesian Inference In Smooth Pursuit Ementioning
confidence: 94%
See 2 more Smart Citations
“…Orban de Xivry et al (2013) demonstrated that Kalman filtering can reproduce the major properties of visually guided smooth pursuit and anticipatory smooth pursuit. A later study demonstrated that the reliability-based integration of prior expectation with visual information occurred not only in smooth pursuits but also in catch-up saccades (Deravet et al, 2018). Similarly, Bogadhi et al (2013) demonstrated that the reliability-weighted dynamic integration of retinal and extra-retinal signals can explain pursuit behaviors during target blanking.…”
Section: Cognitive Control and Bayesian Inference In Smooth Pursuit Ementioning
confidence: 94%
“…The interplay between prior knowledge and sensory evidence was demonstrated in smooth pursuit eye movements by a neurally plausible network model (Yang et al, 2012). More recent studies demonstrated that the integration of a short-term prior for speed and sensory information in smooth pursuit can be explained by Bayesian integration in monkeys (Darlington et al, 2017(Darlington et al, , 2018 and humans (Deravet et al, 2018). These studies primarily investigated the interaction between prior knowledge for motion speed and the precision of the visual motion, and they demonstrated the attraction of pursuit speed toward the prior information (bias).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently an effort has been made to provide a more general theoretical framework, which is based on Bayesian inference and the reliability-based cue combination. Although the mapping of this theoretical framework onto neuronal functions remains to be elucidated, it has the clear advantage of generality, as for instance, it would encompass all forms of smooth pursuit behavior, including prediction-based and visually-guided tracking [42][43][44][45].…”
Section: Anticipatory Smooth Pursuit Eye Movements (Aspem)mentioning
confidence: 99%
“…As shown in this sample screenshot, this was performed by moving a mouse cursor (black triangle) on a continuous rating scale between "Left", to "Unsure" and finally "Right". specific regularities in the properties of visual motion, such as speed, timing or direction [10,44,46]. Second, it is a robust phenomenon, which has been observed on a large population of human participants and even in non-human primates (for a recent review see [47]).…”
Section: Fig 1 Smooth Pursuit Eye Movements and Explicit Direction Pmentioning
confidence: 99%